2013
DOI: 10.1080/01430750.2013.853205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heating the catalytic converter on emission characteristic of gasoline automotive vehicles

Abstract: Gasoline engines have been widely used as engineering machinery, automobile and shipping power equipment due to their excellent drivability and economy. At the same time, gasoline engines are major contributors to various types of air pollutants such as carbon monoxide (CO), oxides of nitrogen (NO x ), and other harmful compounds. With the increasing concern of environment and more stringent government regulation on exhaust emissions, the reduction in engine emissions such as particulate matter and NO x is a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Similar studies are performed by other groups. Tyagi R. K. et al [21] test an electrically heated exhaust cleaning system utilizing a three-cylinder gasoline engine. The findings demonstrate that electrical heating considerably increases the TWC purifying efficiency, lowering CO, THC, and NOx emissions by around 70%, 50%, and 50%, respectively.…”
Section: Application To Gasoline Engine Vehiclesmentioning
confidence: 99%
“…Similar studies are performed by other groups. Tyagi R. K. et al [21] test an electrically heated exhaust cleaning system utilizing a three-cylinder gasoline engine. The findings demonstrate that electrical heating considerably increases the TWC purifying efficiency, lowering CO, THC, and NOx emissions by around 70%, 50%, and 50%, respectively.…”
Section: Application To Gasoline Engine Vehiclesmentioning
confidence: 99%
“…It was concluded that shortening the exhaust pipe increased the inlet temperature, and shortening the light-off time with a retarded ignition timing and increased idle speed had positive effects on reducing the HC and CO emissions' light-off time. Tyagi and Ranjan (2015) studied a preheated catalytic converter. Experimentally, it was observed that the air pollutant exhaust emissions were reduced by preheating the catalytic converter.…”
Section: Introductionmentioning
confidence: 99%
“…Various tests were performed by the heating of catalytic converter to eliminate in the delay period of temperature gain from 0°C to 750°C. It was perceived after the experimental investigation that exhaust emissions such as HC, CO, and NOX reduced significantly with the reduction in delay time [7]. The spark engine catalytic converter conversion efficiency was studied for new, old and without a converter.…”
Section: Introductionmentioning
confidence: 99%